Daam1 regulates fascin for actin assembly in mouse oocyte meiosis. Issue 14 (18th July 2017) - Lu, Yujie; Zhang, Yu; Pan, Meng-Hao; Kim, Nam-Hyung; Sun, Shao-Chen; Cui, Xiang-Shun
ABSTRACT: As a formin protein, Daam1 (Dishevelled-associated activator of morphogenesis 1) is reported to regulate series of cell processes like endocytosis, cell morphology and migration via its effects on actin assembly in mitosis. However, whether Daam1 plays roles in female meiosis remains uncertain. In this study, we investigated the expression and functions of Daam1 during mouse oocyte meiosis. Our results indicated that Daam1 localized at the cortex of oocytes, which was similar with actin filaments. After Daam1 morpholino (MO) microinjection, the expression of Daam1 significantly decreased, which resulted in the failure of oocyte polar body extrusion. These results might be due to the defects of actin assembly, since the decreased fluorescence intensity of actin filaments in oocyte cortex and cytoplasm were observed. However, Daam1 knockdown seemed not to affect the meiotic spindle movement. In addition, we found that fascin might be the down effector of Daam1, since the protein expression of fascin decreased after Daam1 knockdown. Thus, our data suggested that Daam1 affected actin assembly during oocyte meiotic division via the regulation of fascin expression.